Infective Spondylitis - A Complication of Temporary Catheter inPatient Receiving Haemodialysis: A Case Report - Haque, Wasim Md Mohosinul; Samad, Tabassum; Ananna, Mehruba Alam; Rahim, Muhammad Abdur; Iqbal, Sarwar (BIRDEM Medical Journal, 2014)
Infective spondylodiscitis (ISD) is an uncommon, devastating but potentially preventable and treatable condition specially in patients receiving haemodialysis (HD) through central venous (CV) catheters. Here, we present an elderly diabetic patient who was on HD through CV line placed in right femoral vein, who came because of pyrexia and neck pain. Diagnostic workup was in favour of ISD and excluded tuberculosis or malignancy. He responded well to anti-staphylococcal antibiotics. Birdem Med J 2014; 4(2): 108-110